Robust Control of Urban Industrial Water Mismatching Uncertain System - LI Kebai; ZHAO Yuhua (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Urban industrial water system parameter fluctuation producing uncertainty may not occur in a control input channel, can be applied mismatching uncertain system to describe. Based on Lyapunov direct method and linear matrix inequality, design the urban industrial water mismatching uncertain system feedback stabilization robust control scheme. Avoid the defects that the feedback stabilization control method based on the matrix Riccati equation need to preset equation parameters, easier to solve and can reduce the conservative. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2068